An Exploratory Study on the Effects of Psychoeducation in Reducing Parenting Stress among Parents of Autistic Children During the Post-Pandemic Period - Daulay, Nurussakinah (Universitas Mercu Buana Yogyakarta, 2025)
The severity of challenges and limitations experienced by children with autism can lead to caregiver stress and various difficulties for their parents. This research aimed to reduce parenting stress by offering support within a psychoeducational group in a Special School including 24 parents of autistic children. In this context, a quasi-experimental design was adopted using a purposive sampling method. The measuring tool used was the parenting stress scale, such as difficult child and parent-child dysfunctional interaction. Furthermore, the data were analyzed using an independent sample t-test. The results showed that there were significant differences in parenting stress between the psychoeducation (F (1.22) = 8.091; t = 2.863; p <0.05) and the control group (F (1.22) = 0.002; t = 0.370; p > 0.05). The psychoeducation group had lower parenting stress in the post-test (n = 10; M = 9, the 5.60; SD = 13.729) as compared to the pre-test condition (n = 10; M = 120.60, SD = 23.959). The implications contributed to parents' ability to minimize parenting stress, enhancing a positive environment to maximize the developmental outcomes for children with autism.